Battery

By forming convex and concave structures on the positive electrode sheet of the lithium-ion battery and using a specific electrolyte, the poor infiltration and safety of the electrolyte caused by the expansion of the electrode sheet during the battery cycle are solved, and the cycle stability and safety of the battery are improved performance.

CN119208704AInactive Publication Date: 2024-12-27ZHUHAI COSMX BATTERY CO LTD

Patent Information

Application Number
CN202411708041.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the circulation process, lithium-ion batteries have poor electrolyte infiltration, deterioration of interface, cycle failure and reduced safety due to expansion of the electrode sheet.

Method used

By forming convex and concave structures on the positive electrode sheet, combining a specific proportion of chain carboxylic acid ester and cyclic carbonate electrolyte, the adhesion between the separator and the positive electrode sheet is enhanced, and the density of convex parts is regulated to improve the cycle stability of the battery. and safety performance.

Benefits of technology

It effectively reduces the expansion rate of the battery, improves cycle stability, rate performance and safety performance, and ensures the transmission rate of lithium ions and the isolation effect of the diaphragm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208704A_ABST
    Figure CN119208704A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a battery. The battery comprises a positive plate, a negative plate, a diaphragm and an electrolyte, the diaphragm is located between the positive plate and the negative plate, the diaphragm comprises a carrier layer and a gluing layer located on the surface of one side or two sides of the carrier layer, the gluing layer comprises a first gluing layer, the first gluing layer is adjacent to the positive plate, the first gluing layer is distributed on the surface of the carrier layer in a dotted or planar manner, and the first gluing layer is adjacent to the positive plate. The positive plate comprises a first surface and a second surface, the first surface is provided with a plurality of convex parts, the second surface is provided with concave parts corresponding to the convex parts, the ratio of the distance between the circle centers of the adjacent convex parts to the shortest distance between the edges of the adjacent convex parts is 1.05-30, and the electrolyte comprises chain carboxylic ester and cyclic carbonate. The weight ratio of the chain carboxylic ester to the cyclic carbonate is 1.1-10. According to the battery disclosed by the invention, the bonding force between the diaphragm and the positive plate can be enhanced, and the cycling stability, the rate capability and the safety performance of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a battery. Background Art

[0002] In order to meet consumers' demand for the endurance performance of electronic devices, the energy density of lithium-ion batteries needs to be further improved. As the high energy density of lithium-ion batteries increases, the battery design becomes more extreme, often with higher pole surface density and greater battery expansion, facing cycle performance degradation and safety risks. To address these issues, it is necessary to solve abnormalities such as poor electrolyte wetting, interface deterioration, cycle failure, and reduced safety caused by battery expansion and deformation, so as to improve the overall performance of the battery. Summary of the invention

[0003] Research has found that the electrode formed by embossing has a convex surface on one side and a concave surface on the other side. This uneven electrode can solve the problems of large battery expansion rate and poor electrolyte wettability. The uneven electrode can improve the electrolyte retention effect, making it easier for the electrolyte to penetrate the electrode through the space, and can also alleviate the squeezing of the electrode by the expansion of the material during the battery cycle and release the interlayer stress. However, the concave / convex parts produced by the uneven electrode will reduce the contact surface between the electrode and the diaphragm, weaken the bonding force between the diaphragm and the positive and negative electrode materials, make the diaphragm easily detach from the electrode, increase the distance between the positive and negative electrodes, reduce the transmission dynamics, and hinder the transmission path of lithium ions, thereby deteriorating the battery cycle stability and charging rate performance, aggravating the thermal shrinkage of the diaphragm, reducing the isolation effect of the diaphragm, and deteriorating the safety performance of the battery.

[0004] In order to solve the above technical problems of uneven electrode sheets, the present invention provides a battery. The battery of the present invention can enhance the bonding force between the separator and the positive electrode sheet, thereby improving the cycle stability, rate performance and safety performance of the battery.

[0005] In order to achieve the above object, the present invention provides a battery, wherein the battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, the separator is located between the positive electrode sheet and the negative electrode sheet, the separator comprises a carrier layer and a coating layer located on one side or both sides of the carrier layer, the coating layer comprises a first coating layer, the first coating layer is adjacent to the positive electrode sheet, and the first coating layer is distributed on the surface of the carrier layer in a dotted or surface shape; The positive electrode sheet has a first surface and a second surface facing each other in the thickness direction, a plurality of convex portions exist on the first surface of the positive electrode sheet, and concave portions corresponding to the convex portions exist on the second surface, and the ratio of the distance D1 between the centers of adjacent convex portions to the shortest distance D2 between the edges of adjacent convex portions is 1.05-30; The electrolyte includes chain carboxylates and cyclic carbonates, the chain carboxylates include one or more of propyl propionate, propyl acetate, isopropyl acetate, ethyl acetate, ethyl butyrate and methyl propionate, the cyclic carbonate includes propylene carbonate and / or ethylene carbonate, and the weight ratio of the chain carboxylates to the cyclic carbonate is 1.1-10.

[0006] Through the above technical solution, the present invention has at least the following advantages compared with the prior art: (1) The protrusions provided on the positive electrode sheet of the present invention can provide reserved space for the expansion of the negative electrode material, thereby reducing the expansion rate of the battery.

[0007] (2) The battery of the present invention can improve the bonding force between the positive electrode sheet and the separator by controlling the weight ratio of the cyclic carbonate to the chain carbonate in the electrolyte, thereby improving the rate performance, cycle stability and safety performance of the battery; on the other hand, it can improve the transmission rate of lithium ions, thereby improving the cycle stability and rate performance of the battery. The density of the protrusions can be regulated by controlling the ratio of the distance D1 between the centers of adjacent protrusions to the shortest distance D2 between the edges of adjacent protrusions. The electrolyte of the present invention can achieve a good adaptation to the density of the protrusions, thereby effectively improving the bonding force between the positive electrode sheet having protrusions at this density and the separator, thereby improving the cycle stability, rate performance and safety performance of the battery.

[0008] Other features and advantages of the present invention will be described in detail in the following detailed description.

[0009] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 Shown is one of the schematic diagrams of the first surface of the positive electrode sheet of the present invention.

[0011] Figure 2 Shown is the second schematic diagram of the first surface of the positive electrode sheet of the present invention.

[0012] Figure 3 Shown is a schematic cross-sectional view of the positive electrode sheet of the present invention. DETAILED DESCRIPTION

[0013] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention. In this article, unless otherwise specified, the data range includes the endpoints.

[0014] It should be noted that the numerical expressions such as "first" and "second" in the present disclosure are only used to distinguish different substances or usage methods, and do not represent the difference in order.

[0015] The present invention provides a battery, wherein the battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, wherein the separator comprises a carrier layer and a coating layer located on one side or both sides of the carrier layer, wherein the coating layer comprises a first coating layer, wherein the first coating layer is adjacent to the positive electrode sheet, and wherein the first coating layer is distributed on the surface of the carrier layer in a dotted or planar manner; The positive electrode sheet has a first surface and a second surface facing each other in the thickness direction, a plurality of convex portions exist on the first surface of the positive electrode sheet, and concave portions corresponding to the convex portions exist on the second surface, and the ratio of the distance D1 between the centers of adjacent convex portions to the shortest distance D2 between the edges of adjacent convex portions is 1.05-30; The electrolyte includes chain carboxylates and cyclic carbonates, wherein the chain carboxylates include one or more of propyl propionate (PP), propyl acetate (EP), isopropyl acetate, ethyl acetate, ethyl butyrate and methyl propionate, and the cyclic carbonate includes propylene carbonate and / or ethylene carbonate, and the weight ratio of the chain carboxylates to the weight of the cyclic carbonate is 1.1-10.

[0016] like Figure 1 , Figure 2 and Figure 3 As shown, the first surface of the positive electrode sheet has a plurality of protrusions 1, and the second surface has concave portions 2 corresponding to the protrusions 1. The protrusions and concave portions can be prepared by special rolling processing such as embossing.

[0017] The first adhesive coating layer can be distributed on the surface of the carrier layer in a dot-like or surface-like manner, that is, a first adhesive coating layer with full coverage or non-full coverage is formed on the surface of the carrier layer. The first adhesive coating layer is distributed on the surface of the carrier layer in a dot-like manner or the entire surface of the carrier layer is covered by the first adhesive coating layer.

[0018] The present invention controls the weight ratio of the chain carboxylic acid ester to the cyclic carbonate ester to be 1.1-10 (1.1, 1.5, 2, 3, 4, 5, 6, 7, 8, 9 or 10), so that the chain carboxylic acid ester easily enters between the polymer chains of the coating layer, has a certain swelling effect on the coating layer in the separator, improves the adhesion of the coating layer, and can form a three-dimensional network structure in the coating layer through hydrogen bonding, electrostatic interaction and hydrophobic interaction. The three-dimensional network structure can improve the interaction between the positive electrode sheet and the separator, thereby improving the stability of the interface between the positive electrode sheet and the separator. Qualitatively, it provides a smooth path for the transmission of lithium ions. Since cyclic carbonates are difficult to enter between polymer chains, it is not conducive to improving the adhesion of the coating layer. However, it has good chemical stability. The addition of cyclic carbonates can adjust the bonding force between the separator coating layer and the positive electrode to prevent the increase of battery internal resistance and slow ion flow due to excessive bonding force. By controlling the ratio of carboxylic acid esters and cyclic carbonates within a certain range, the bonding of the glue layer can be appropriately improved to compensate for the deterioration of the contact between the positive electrode sheet and the separator caused by embossing, thereby improving the cycle stability, rate performance and safety performance of the battery; At the same time, by controlling the ratio of the distance D1 between the centers of adjacent protrusions and the shortest distance D2 between the edges of adjacent protrusions to 1.05-30 (1.05, 1.5, 2, 5, 8, 10, 12, 15, 18, 20, 22, 25, 28 or 30), the density of the protrusions can be controlled, so that the density of the protrusions and the electrolyte can achieve a better fit, so that the electrolyte can effectively improve the adhesion between the positive electrode sheet and the separator at the density of the protrusions, thereby further improving the cycle stability, rate performance and safety performance of the battery; when the distance D1 between the centers of adjacent protrusions and the shortest distance D2 between the edges of adjacent protrusions is ... When the ratio is lower than 1.05, the density of the protrusions is too dense and the reserved space is too small, which cannot effectively alleviate the squeezing of the electrode sheet by the expansion of the negative electrode material during the cycle; when the ratio of the distance D1 between the centers of adjacent protrusions to the shortest distance D2 between the edges of adjacent protrusions is higher than 30, the density of the protrusions is too low. In order to improve the adhesion between the positive electrode sheet and the separator, a large amount of chain carboxylic acid esters is required, but a large amount of chain carboxylic acid esters will reduce the viscosity of the electrolyte. Even with a large amount of cyclic carbonates, the viscosity of the electrolyte cannot be reduced to an appropriate level, which affects the transmission rate of lithium ions in the electrolyte and reduces the cycle stability, rate performance and safety performance of the battery.

[0019] In the present invention, by providing convex portions on the positive electrode sheet and controlling the density of the convex portions and the weight ratio of the cyclic carbonate to the chain carboxylic acid ester in the electrolyte, the cycle stability, rate performance and safety performance of the battery can be improved compared with the prior art. In order to further improve the effect, one or more of the technical features can be further optimized.

[0020] In the present invention, the distance D1 between the centers of adjacent convex parts indicates that when the convex part is circular, D1 is the distance between the centers of adjacent convex parts, and when the convex part is non-circular, the center of the circumscribed circle of the convex part is taken as the center of the convex part, that is, D1 is the center of the circumscribed circle of the adjacent convex part. The shortest distance D2 between the edges of adjacent convex parts indicates the shortest distance between any two points on the edges of adjacent convex parts.

[0021] In one example, a ratio of a distance D1 between centers of adjacent protrusions to a shortest distance D2 between edges of adjacent protrusions is 1.1-20.

[0022] In one example, the weight ratio of the linear carboxylic acid ester to the cyclic carbonate is 1.5-5 (eg, 1.5, 2, 2.5, 3, 3.3, 3.5, 3.8, 4, 4.3, 4.5, 4.8 or 5).

[0023] According to a specific embodiment, the ratio of the distance D1 between the centers of adjacent protrusions to the shortest distance D2 between the edges of adjacent protrusions is 1.1-20, and the ratio of the weight of the linear carboxylate to the weight of the cyclic carbonate is 1.5-5.

[0024] In one example, D1 is 2 mm-10 mm (eg, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, or 10 mm).

[0025] In one example, D1 is 3 mm-8 mm.

[0026] In the present invention, the distance D1 between the centers of adjacent protrusions can be obtained by the following test method: arbitrarily select 10-20 (for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20) protrusions on the first surface of the positive electrode sheet, test the distance between the centers of adjacent protrusions among the above 10-20 protrusions, and take the average value thereof as D1.

[0027] In the present invention, the distance D1 between the centers of any two adjacent protrusions may be the same or different.

[0028] In one example, D2 is 0.2 mm-8 mm (e.g., 0.2 mm, 0.5 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm or 8 mm). Controlling D2 within the above range can make the density of the protrusions moderate, meet the deformation space required for the expansion of the negative electrode material and the requirements of the electrolyte for the wetting effect, thereby reducing the expansion rate of the battery and improving the cycle stability and rate performance of the battery.

[0029] In one example, D2 is 1 mm-4 mm.

[0030] In the present invention, the shortest distance D2 between the edges of adjacent protrusions can be obtained by the following test method: arbitrarily select 10-20 (for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20) protrusions on the first surface of the positive electrode sheet, test the shortest distance between the edges of adjacent protrusions among the above 10-20 protrusions, and take the average value thereof as D2.

[0031] In the present invention, the shortest distance D2 between the edges of any two adjacent protrusions may be the same or different.

[0032] According to a specific implementation, D1 is 2 mm-10 mm, D2 is 0.2 mm-8 mm, and the ratio of the distance D1 between the centers of adjacent convex portions to the shortest distance D2 between the edges of adjacent convex portions is 1.05-30.

[0033] According to a specific implementation, D1 is 3 mm-8 mm, D2 is 1 mm-4 mm, and the ratio of the distance D1 between the centers of adjacent convex portions to the shortest distance D2 between the edges of adjacent convex portions is 1.1-20.

[0034] In one example, based on the total weight of the electrolyte, the weight content of the linear carboxylic acid ester is 10%-55% (e.g., 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or 55%).

[0035] In one example, based on the total weight of the electrolyte, the weight content of the chain carboxylic acid ester is 15%-45%.

[0036] In one example, based on the total weight of the electrolyte, the weight content of the cyclic carbonate is 5%-35% (eg, 5%, 10%, 15%, 20%, 25%, 30% or 35%).

[0037] In one example, based on the total weight of the electrolyte, the weight content of the cyclic carbonate is 8%-20%.

[0038] According to a specific embodiment, based on the total weight of the electrolyte, the weight content of the chain carboxylate is 10%-55%, the weight content of the cyclic carbonate is 5%-35%, and the weight ratio of the chain carboxylate to the cyclic carbonate is 1.1-10.

[0039] According to a specific embodiment, based on the total weight of the electrolyte, the weight content of the chain carboxylate is 15%-45%, the weight content of the cyclic carbonate is 8%-20%, and the weight ratio of the chain carboxylate to the cyclic carbonate is 1.5-5.

[0040] According to a specific embodiment, D1 is 2mm-10mm, D2 is 0.2mm-8mm, the ratio of the distance D1 between the centers of adjacent protrusions to the shortest distance D2 between the edges of adjacent protrusions is 1.05-30, and based on the total weight of the electrolyte, the weight content of the chain carboxylate is 10%-40%, the weight content of the cyclic carbonate is 5%-35%, and the ratio of the weight of the chain carboxylate to the weight of the cyclic carbonate is 1.1-10.

[0041] According to a specific embodiment, D1 is 3mm-8mm, D2 is 1mm-4mm, the ratio of the distance D1 between the centers of adjacent protrusions to the shortest distance D2 between the edges of adjacent protrusions is 1.1-20, and based on the total weight of the electrolyte, the weight content of the chain carboxylate is 15%-35%, the weight content of the cyclic carbonate is 8%-20%, and the ratio of the weight of the chain carboxylate to the weight of the cyclic carbonate is 1.5-5.

[0042] In one example, the first coating layer includes one or more of polyethylene oxide, polyethylene wax, polypropylene oxide, polyetherimide, vinylidene fluoride polymer, polyacrylonitrile, acrylate polymer, acrylic polymer and aramid.

[0043] In one example, the vinylidene fluoride polymer includes one or more of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-vinylidene fluoride copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, and vinylidene fluoride-trifluoroethylene copolymer.

[0044] In one example, the acrylic polymer includes one or more of polymethyl methacrylate, polyethyl acrylate, and polybutyl acrylate.

[0045] In one example, the first coating layer has a thickness of 0.5 μm-8 μm (eg, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm).

[0046] In one example, the thickness of the first coating layer is 1 μm-2.5 μm.

[0047] In one example, based on the surface area of ​​the carrier layer, the orthographic projection area of ​​the first coating layer on the carrier layer accounts for 25%-100% (for example, 25%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or 100%).

[0048] In one example, the coating layer further includes a second coating layer, and the second coating layer is adjacent to the negative electrode sheet.

[0049] In one example, the carrier layer includes a substrate layer and a ceramic layer located on one side or both sides of the substrate layer.

[0050] In one example, the substrate layer includes one or more of polyolefin, polyolefin alcohol, polyamide, polyolefin ester, polydopamine and polyolefin nitrile.

[0051] In one example, the ceramic layer includes inorganic particles, and the inorganic particles include one or more of aluminum oxide, aluminum hydroxide, boehmite, silicon oxide, titanium oxide, barium sulfate, silicon nitride, aluminate, aluminum nitride, and zirconium oxide.

[0052] In one example, the ceramic layer further includes a separator binder.

[0053] In one example, the separator binder includes one or more of polyvinylidene fluoride, polyethylene oxide, and polyacrylate.

[0054] In one example, based on the total weight of the ceramic layer, the weight content of the inorganic particles is 84%-99% (84%, 85%, 87%, 90%, 92%, 95%, 97% or 99%), and the weight content of the diaphragm binder is 1%-15% (1%, 3%, 5%, 8%, 10%, 13% or 15%).

[0055] In one example, based on the total weight of the ceramic layer, the weight content of the inorganic particles is 90%-98%, and the weight content of the separator binder is 2%-10%.

[0056] In one example, the ceramic layer has a thickness of 1 μm-8 μm (eg, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, or 8 μm).

[0057] In one example, the thickness of the separator is 2 μm-20 μm (eg, 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, or 20 μm).

[0058] In one example, the thickness of the separator is 5 μm-12 μm.

[0059] In one example, the electrolyte further includes ethyl 2,2-difluoroacetate (DFEA).

[0060] In one example, based on the total weight of the electrolyte, the weight content of ethyl 2,2-difluoroacetate is 1%-20% (for example, 1%, 3%, 5%, 8%, 10%, 13%, 15%, 18% or 20%). Controlling the weight content of DFEA in the electrolyte within the above range can further reduce the viscosity of the electrolyte, improve the wettability of the electrolyte to the diaphragm and the electrode, and improve the ion transfer efficiency, while ensuring good interface stability between the positive electrode and the diaphragm, thereby further improving the cycle stability and rate performance of the battery. When the weight content of DFEA in the electrolyte is less than 1wt%, the effect of improving the viscosity of the electrolyte is low, and the battery dynamics does not change significantly. When the weight content of DFEA in the electrolyte is greater than 20wt%, DFEA decomposes in large quantities at the electrode interface to form an overly thick SEI component, which deteriorates the battery dynamics performance.

[0061] In one example, based on the total weight of the electrolyte, the weight content of the ethyl 2,2-difluoroacetate is 5%-15%.

[0062] In one example, the ratio Z of the weight of the ethyl 2,2-difluoroacetate to the weight of the chain carboxylate is 0.1-2 (for example, 0.1, 0.3, 0.5, 0.8, 1, 1.3, 1.5, 1.8 or 2). Controlling Z within the above range can reduce the viscosity of the electrolyte, improve the wettability of the electrolyte, and also reduce the freezing point of the electrolyte, which can improve the low-temperature discharge performance of the battery, improve the low-temperature discharge capacity retention rate, and ensure the adhesion between the diaphragm and the positive electrode sheet. When Z < 0.5, the amount of DFEA is too low, and the improvement of the low-temperature discharge performance of the battery is not obvious; when Z > 5, the amount of DFEA is too high, which reduces the polarity of the electrolyte, reduces the permeability of the electrolyte to the diaphragm, and reduces the adhesion of the diaphragm to the positive electrode sheet.

[0063] In one example, the ratio Z of the weight of the ethyl 2,2-difluoroacetate to the weight of the linear carboxylate is 0.2-1.

[0064] According to a specific embodiment, based on the total weight of the electrolyte, the weight content of the chain carboxylic acid ester is 10%-40%, the weight content of the ethyl 2,2-difluoroacetate is 1%-20%, and the ratio Z of the weight of the ethyl 2,2-difluoroacetate to the weight of the chain carboxylic acid ester is 0.1-2.

[0065] According to a specific embodiment, based on the total weight of the electrolyte, the weight content of the chain carboxylic acid ester is 15%-35%, the weight content of the ethyl 2,2-difluoroacetate is 5%-15%, and the ratio Z of the weight of the ethyl 2,2-difluoroacetate to the weight of the chain carboxylic acid ester is 0.2-1.

[0066] In one example, the electrolyte further includes a lithium salt, an organic solvent and an additive.

[0067] In one example, the lithium salt includes one or more of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium bisfluorosulfonyl imide (LiTFSI), lithium bistrifluoromethylsulfonyl imide, lithium difluorobisoxalatophosphate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyllithium and lithium bis(trifluoromethylsulfonyl)imide.

[0068] In one example, the organic solvent includes one or more of diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC).

[0069] In one example, the additive includes one or more of fluoroethylene carbonate (FEC), 1,3-propane sultone (PS), 1,3-acrylonitrile lactone (PST), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), dithiodiphenyl ether sulfate (DTD), 4-methyl-vinyl sulfate, tris-propargyl phosphate and 1,3,6-hexane trinitrile.

[0070] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 8%-22% (e.g., 8%, 10%, 12%, 15%, 18%, 20% or 22%), the weight content of the organic solvent is 0%-30% (e.g., 0%, 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25% or 30%), and the weight content of the additive is 0.1%-35% (0.1%, 0.5%, 1%, 3%, 5%, 8%, 10%, 13%, 15%, 18%, 20%, 23%, 25%, 28%, 30%, 33% or 35%). When the weight content of the organic solvent in the electrolyte is 0%, it means that there is no organic solvent in the electrolyte.

[0071] In one example, based on the total weight of the electrolyte, the weight content of the lithium salt is 10%-17%, the weight content of the organic solvent is 0%-20%, and the weight content of the additive is 5%-30%.

[0072] In one example, the height H of the convex portion is 3 μm-40 μm (e.g., 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm). The heights of the convex portions in the convex portion region may be the same or different. When the heights of the convex portions in the convex portion region are the same, it means that the heights of all the convex portions in the convex portion region are the same. When the heights of the convex portions in the convex portion region are different, it means that there are convex portions with different heights in the convex portion region.

[0073] By controlling the height of the convex portion within the above range, sufficient deformation space can be reserved for the expansion of the negative electrode material while causing less damage to the positive electrode sheet, thereby reducing the expansion rate of the battery and improving the cycle stability of the battery. When the height H of the convex portion is less than 3 μm, the deformation space reserved for the expansion of the negative electrode material is insufficient, and the increase in the battery expansion rate caused by the expansion of the negative electrode material cannot be effectively improved; when the height H of the convex portion is higher than 40 μm, the height of the convex portion is too large, causing greater damage to the positive electrode sheet.

[0074] In one example, the height H of the protrusion is 5 μm-30 μm.

[0075] In the present invention, the height of the convex portion can be obtained by SEM testing, as follows: 10-20 (for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20) convex portions are randomly selected on the first surface of the positive electrode sheet, and the heights of the 10-20 convex portions are tested, and the average value thereof is taken as H.

[0076] In the present invention, the heights of any two protrusions may be the same or different.

[0077] In one example, the first surface includes a convex region 3, and the convex region 3 includes a convex portion 1. The area of ​​the convex region 3 may occupy the entire surface area of ​​the first surface (e.g., Figure 2 The area of ​​the convex region 3 may also occupy part of the surface area of ​​the first surface (as shown in FIG. Figure 1 When the area of ​​the convex region occupies a part of the surface area of ​​the first surface, the first surface further includes a non-convex region.

[0078] It can be understood that the concave portion of the second surface corresponds to the convex portion of the first surface, and therefore, the second surface includes a concave portion area, and the concave portion area includes the concave portion. The area of ​​the concave portion area can occupy the entire surface area of ​​the second surface. The area of ​​the concave portion area can also occupy a partial surface area of ​​the second surface. Similarly, when the area of ​​the concave portion area occupies a partial surface area of ​​the second surface, the second surface also includes a non-convex portion area.

[0079] In one example, the number of protrusions in any 1 cm×1 cm area selected in the protrusion area is 2-25 (for example, 2, 5, 8, 10, 12, 15, 18, 20, 22 or 25). Controlling the number of the protrusions within the above range can make the density of the protrusions moderate and achieve a better fit with the electrolyte, thereby reserving sufficient deformation space for the expansion of the negative electrode material while ensuring the bonding force between the positive electrode sheet and the separator, thereby reducing the expansion rate of the battery and improving the cycle performance, rate performance and safety performance of the battery. When the number of protrusions is less than 2, it is impossible to reserve sufficient deformation space for the expansion of the negative electrode material; when the number of protrusions is greater than 25, the density of the protrusions is too dense and cannot achieve a good fit with the electrolyte, thereby reducing the cycle performance and rate performance of the battery.

[0080] In one example, the number of convex portions in an area of ​​1 cm×1 cm randomly selected from the convex portion region is 4-12.

[0081] In one example, on the first surface, the area of ​​the orthographic projection of the convex portion on the first surface accounts for 2%-85% (for example, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85%). Controlling the area of ​​the orthographic projection of the convex portion on the first surface on the first surface to be within the above range can alleviate the volume expansion of the negative electrode material, reduce the expansion rate of the battery, improve the wettability of the electrolyte, and improve the cycle stability and rate performance of the battery. When the area of ​​the orthographic projection of the convex portion on the first surface on the surface of the positive electrode sheet accounts for less than 2%, the wettability of the electrolyte to the positive electrode sheet cannot be effectively improved, affecting the cycle stability and rate performance of the battery; when the area of ​​the orthographic projection of the convex portion on the first surface on the surface of the positive electrode sheet accounts for more than 85%, the volume energy density of the battery is greatly lost, and the adhesion between the diaphragm and the electrode sheet is reduced, resulting in reduced cycle stability and safety performance of the battery.

[0082] In one example, on the first surface, the area of ​​the orthographic projection of the convex portion on the first surface accounts for 15%-40%.

[0083] In the present invention, the area ratio of the orthographic projection of the convex portion on the first surface is the ratio of the sum of the orthographic projection areas of all the convex portions on the first surface.

[0084] According to a specific embodiment, D1 is 2mm-10mm, D2 is 0.5mm-8mm, the ratio of the distance D1 between the centers of adjacent protrusions to the shortest distance D2 between the edges of adjacent protrusions is 1.05-30, the height H of the protrusions is 3μm-40μm, the number of protrusions is 2-25 within an area of ​​1cm×1cm selected at random in the protrusion area, and on the surface of the positive electrode sheet, the area of ​​the orthographic projection of the protrusion on the surface of the positive electrode sheet accounts for 2%-85%.

[0085] According to a specific embodiment, D1 is 3mm-8mm, D2 is 1mm-4mm, the ratio of the distance D1 between the centers of adjacent protrusions to the shortest distance D2 between the edges of adjacent protrusions is 1.1-20, the height H of the protrusions is 5μm-30μm, the number of protrusions in an arbitrarily selected 1cm×1cm area in the protrusion area is 4-12, and on the first surface, the area of ​​the orthographic projection of the protrusions on the first surface accounts for 15%-40%.

[0086] In one example, the shape of the orthographic projection of the convex portion on the first surface includes a regular pattern (such as Figure 1 as shown) and / or irregular patterns.

[0087] In one example, the regular shape includes one or more of a circle, an ellipse, a square, a rectangle and a polygon.

[0088] In one example, the projections of the convex portions on the first surface are distributed in a matrix (eg Figure 1 and Figure 2 as shown).

[0089] In one example, the bonding force between the positive electrode sheet and the separator is 2 N / m-25 N / m (eg, 2 N / m, 5 N / m, 10 N / m, 15 N / m, 20 N / m or 25 N / m).

[0090] In one example, the bonding force between the positive electrode sheet and the separator is 3N / m-15N / m.

[0091] In the present invention, the bonding force between the positive electrode sheet and the diaphragm can be tested by the following method: first, the finished battery is disassembled, the part where the positive electrode sheet and the diaphragm are bonded to each other is taken out, and it is cut into 2mm×2mm samples, the free end of the sample is folded 180°, and the bonding surface is peeled off by about 50mm; the two ends of the peeled bonding surface are respectively fixed on both sides of a peeling force tester, the instrument is started to peel off the free end of the sample, and the bonding force is directly obtained from the testing instrument.

[0092] In one example, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, and the positive electrode active material includes a lithium cobalt oxide material.

[0093] In one example, the lithium cobalt oxide material is a doped and / or modified lithium cobalt oxide material.

[0094] In one embodiment, the lithium cobalt oxide material includes a chemical formula of LiCo 1-d-e M d N e O2 particles.

[0095] Wherein, 0.01≤d≤0.1 (e.g., 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, or 0.1), 0≤e≤0.05 (e.g., 0, 0.01, 0.02, 0.03, 0.04, or 0.05). When e is 0, it means that N does not exist.

[0096] M may include Mn and / or Al.

[0097] N may include one or more of Na, Mg, Zr, Ni, Y, Sr, W, Sc, B, W, Si, Ti, Zr, Sr, Sn, Tb, Nb, Sb, Se, Ce, and Te.

[0098] In one example, the median particle size Dv50 of the lithium cobalt oxide material is 8 μm-25 μm (eg, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, 23 μm or 25 μm).

[0099] In the present invention, the median particle size can be obtained by testing with a laser particle size analyzer.

[0100] In one example, the positive electrode active material layer further includes a positive electrode conductor and a positive electrode binder.

[0101] In one example, the positive electrode conductive agent includes one or more of conductive carbon black (Super P), conductive carbon fiber, carbon nanotube and graphene.

[0102] In one example, the positive electrode binder includes one or more of polyvinylidene fluoride (PVDF), styrene-butadiene rubber, carboxymethyl cellulose, polyacrylate, and polyvinyl alcohol.

[0103] In one example, based on the total weight of the positive electrode active material layer, the weight content of the positive electrode active material is 95%-99.5% (for example, 95%, 96%, 97%, 98%, 99% or 99.5%), the weight content of the positive electrode conductor is 0.3%-3% (for example, 0.3%, 0.5%, 1%, 1.5%, 2%, 2.5% or 3), and the weight content of the positive electrode binder is 0.2%-2% (for example, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8% or 2%).

[0104] In one example, based on the total weight of the positive electrode active material layer, the weight content of the positive electrode active material is 96%-99%, the weight content of the positive electrode conductor is 1.2%-2%, and the weight content of the positive electrode binder is 0.8%-2%.

[0105] In one example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on one side or both sides of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material.

[0106] In one example, the negative electrode active material includes one or more of graphite, hard carbon, soft carbon, silicon carbon, silicon oxygen and graphene.

[0107] In one example, the negative electrode active material includes a doping element, and the doping element includes one or more of Fe, Cu, Ca, Ni and Na.

[0108] In one example, the weight ratio of the doping element in the negative electrode active material is 10 ppm-80 ppm (for example, 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm, 60 ppm, 70 ppm or 80 ppm).

[0109] In one example, the negative electrode active material layer further includes a positive electrode conductor and a positive electrode binder.

[0110] In one example, the negative electrode conductive agent includes one or more of conductive graphite, conductive carbon black, carbon nanotubes, and graphene.

[0111] In one example, the negative electrode binder includes one or more of polyvinylidene fluoride, styrene butadiene rubber, carboxymethyl cellulose, polyacrylate and polyvinyl alcohol.

[0112] In one example, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode active material is 85%-99% (for example, 85%, 87%, 90%, 92%, 95%, 97% or 99%), the weight content of the negative electrode conductor is 0.5%-10% (for example, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%), and the weight content of the negative electrode binder is 0.5%-15% (0.5%, 1%, 3%, 5%, 8%, 10%, 13% or 15%).

[0113] In one example, based on the total weight of the negative electrode active material layer, the weight content of the negative electrode active material is 95%-98%, the weight content of the negative electrode conductor is 1.2%-3%, and the weight content of the negative electrode binder is 0.8%-2%.

[0114] The battery may be a lithium ion battery.

[0115] The battery may be a lithium ion secondary battery.

[0116] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0117] The following examples are provided to illustrate the batteries of the present invention.

[0118] Example 1 (1) Positive electrode Positive electrode active material: lithium cobalt oxide (doped with Mg and Al, with a median particle size of 17 μm) 97.5 parts by weight; Positive electrode conductive agent: 1.3 parts by weight in total of Super P and carbon nanotubes (wherein the mass ratio of Super P to carbon nanotubes is 1:1); Positive electrode binder: polyvinylidene fluoride (PVDF 520) 1.2 parts by weight; The positive electrode active material, positive electrode binder, and positive electrode conductive agent are mixed in N-methylpyrrolidone (NMP) solvent and continuously stirred in a stirrer to form a uniform positive electrode slurry. Subsequently, the positive electrode slurry is coated on both sides of a positive electrode current collector (aluminum foil) with a thickness of 12μm, and placed in a 120℃ vacuum oven to dry for 6h, and then rolled and cut to obtain the required positive electrode sheet.

[0119] The electrode sheet is obtained by pressing with a mold to form specific concave and / or convex portions on the surface of the electrode sheet. Among them, the distance D1 between the centers of adjacent convex portions is 4.1 mm, and the shortest distance D2 between the edges of adjacent convex portions is 2.2 mm, then D1 / D2=1.86, the height H of the convex portion is 29.4 μm, and the number of convex portions in an area of ​​1 cm×1 cm is 9 (the number of convex portions in Example 10f in Example 2 to Example 10 is adaptively adjusted when the number of convex portions changes, and will not be repeated below), and the orthographic projection area of ​​the convex portion on the first surface accounts for 30.3%.

[0120] (2) Negative electrode Negative electrode active material: 81.5 parts by weight of graphite, 15 parts by weight of silicon carbon, a total of 96.5 parts by weight; Negative electrode conductive agent: 1.5 parts by weight of carbon nanotubes; Negative electrode binder: 1 part by weight of sodium carboxymethyl cellulose (CMC), 1 part by weight of styrene-butadiene rubber (SBR); The negative electrode active material and negative electrode binder are mixed in a water solvent and continuously stirred in a stirrer to form a uniform and flowing negative electrode slurry. Subsequently, the slurry is coated on both sides of a negative electrode current collector (copper foil) with a thickness of 10 μm, and dried in a 120°C vacuum oven for 6 hours, and then rolled and cut to obtain the required negative electrode sheet.

[0121] (3) Electrolyte Lithium salt: LiPF6 15 parts by weight; Chain carboxylic acid ester: 20 parts by weight of propyl propionate (PP), 20 parts by weight of ethyl propionate, a total of 40 parts by weight; Cyclic carbonate: 10 parts by weight of propylene carbonate; the weight ratio of chain carboxylic acid ester to cyclic carbonate is 4; Organic solvent: 20 parts by weight of dimethyl carbonate; Additives: 4 parts by weight of 1,3-propane sultone, 3 parts by weight of 1,3,6-hexane trinitrile, and 8 parts by weight of fluoroethylene carbonate (FEC), a total of 15 parts by weight.

[0122] In a glove box filled with argon (water content <1ppm, oxygen content <1ppm), the chain carboxylic acid ester, cyclic carbonate and organic solvent are mixed into a uniform mixed solution, lithium salt and additives are slowly added to the mixed solution, and after stirring evenly, the desired lithium-ion battery electrolyte is obtained.

[0123] (4) Diaphragm After coating a 1.5μm boehmite layer (ceramic layer) on one side of a 5μm polyethylene substrate, 1.8μm polyvinylidene fluoride adhesive layers are coated on both sides, wherein the side coated with the boehmite layer is the first adhesive layer, the first adhesive layer is adjacent to the positive electrode sheet, the thickness of the first adhesive layer is 1.8μm, and the orthographic projection area of ​​the first adhesive layer on the carrier layer accounts for 65.2%.

[0124] (5) Preparation of lithium-ion batteries The positive electrode sheet of step (1), the separator of step (4), and the negative electrode sheet of step (2) are wound to prepare a bare cell, which is then fixed with adhesive tape. The bare cell is then placed in an aluminum-plastic film package, and the electrolyte of step (3) is injected into the dried bare cell. After vacuum packaging, room temperature standing, and high-temperature formation, the desired lithium-ion battery is obtained.

[0125] The thickness expansion rate of the lithium ion battery of Example 1 was measured to be 5.24%, and the low temperature capacity retention rate was 75.25%.

[0126] Example 2 The method was carried out in accordance with Example 1, except that ethyl 2,2-difluoroacetate (DFEA) was added to the electrolyte, wherein the weight content of DFEA in the electrolyte was 15%, and the ratio Z of the weight of ethyl 2,2-difluoroacetate to the weight of the chain carboxylic acid ester was 0.38.

[0127] The low temperature capacity retention rate of the lithium ion battery of Example 2 was measured to be 78.43%.

[0128] Example 3 This embodiment is used to illustrate that different combinations of parameter values ​​can still achieve the effects of the present invention.

[0129] Refer to Example 1, except that the weight content of the chain carboxylate in the electrolyte is 30%, the weight content of the cyclic carbonate is 9%, and the weight ratio of the chain carboxylate to the cyclic carbonate is 3.3; the distance D1 between the centers of adjacent protrusions is 7.3 mm, and the shortest distance D2 between the edges of adjacent protrusions is 3.7 mm, then D1 / D2=1.97, the height H of the protrusion is 17.1 μm, and the orthographic projection area of ​​the protrusion on the first surface accounts for 65.4%; the thickness of the first coating layer is 0.9 μm, and the orthographic projection area of ​​the first coating layer on the carrier layer accounts for 88.7%.

[0130] Example 4 This embodiment is used to illustrate that different combinations of parameter values ​​can still achieve the effects of the present invention.

[0131] Refer to Example 1, except that the weight content of the chain carboxylate in the electrolyte is 50%, the weight content of the cyclic carbonate is 6%, and the weight ratio of the chain carboxylate to the cyclic carbonate is 8.3; the distance D1 between the centers of adjacent protrusions is 9.5 mm, and the shortest distance D2 between the edges of adjacent protrusions is 6.6 mm, then D1 / D2=1.44, the height H of the protrusion is 36.3 μm, and the orthographic projection area of ​​the protrusion on the first surface accounts for 8.3%; the thickness of the first coating layer is 5.7 μm, and the orthographic projection area of ​​the first coating layer on the carrier layer accounts for 47.3%.

[0132] Example 5 The process is carried out in accordance with Example 1, except that the proportion of the orthographic projection area of ​​the first adhesive layer on the carrier layer is adjusted to 100%.

[0133] Example 6 Group This group of examples is used to illustrate the effects produced when the weight ratio of the linear carboxylic acid ester to the cyclic carbonate ester is changed.

[0134] Example 6a The method is carried out in accordance with Example 1, except that the weight content of the linear carboxylate in the electrolyte is 40%, the weight content of the cyclic carbonate is 6%, and the ratio of the weight of the linear carboxylate to the weight of the cyclic carbonate is 6.7.

[0135] Example 6b The method is carried out in accordance with Example 1, except that the weight content of the linear carboxylate in the electrolyte is 45%, the weight content of the cyclic carbonate is 10%, and the ratio of the weight of the linear carboxylate to the weight of the cyclic carbonate is 4.5.

[0136] Example 6c The process is carried out in accordance with Example 1, except that the weight content of the linear carboxylate in the electrolyte is 40%, the weight content of the cyclic carbonate is 8%, and the ratio of the weight of the linear carboxylate to the weight of the cyclic carbonate is 5.

[0137] Example 6d The method is carried out in accordance with Example 1, except that the weight content of the linear carboxylate in the electrolyte is 25%, the weight content of the cyclic carbonate is 20%, and the ratio of the weight of the linear carboxylate to the weight of the cyclic carbonate is 1.3.

[0138] Example 6e The method is carried out in accordance with Example 1, except that the weight content of the linear carboxylate in the electrolyte is 55%, the weight content of the cyclic carbonate is 15%, and the ratio of the weight of the linear carboxylate to the weight of the cyclic carbonate is 3.7.

[0139] Example 6f The same method is used as in Example 1, except that the weight content of the linear carboxylate in the electrolyte is 50%, the weight content of the cyclic carbonate is 5%, and the ratio of the weight of the linear carboxylate to the weight of the cyclic carbonate is 10.

[0140] Example 6g The method is carried out in accordance with Example 1, except that the weight content of the linear carboxylate in the electrolyte is 35%, the weight content of the cyclic carbonate is 4%, and the ratio of the weight of the linear carboxylate to the weight of the cyclic carbonate is 8.8.

[0141] Example 7 Group This group of examples is used to illustrate the effects when the ratio Z of the weight of ethyl 2,2-difluoroacetate to the weight of the linear carboxylic acid ester is changed.

[0142] Example 7a The method is carried out in accordance with Example 2, except that the weight content of the linear carboxylate in the electrolyte is 40%, the weight content of the cyclic carbonate is 10%, the weight content of DFEA is 5%, and the ratio Z of the weight of ethyl 2,2-difluoroacetate to the weight of the linear carboxylate is 0.13.

[0143] The low-temperature capacity retention rate of the lithium-ion battery of Example 7a was measured to be 73.86%.

[0144] Example 7b The method is carried out in accordance with Example 2, except that the weight content of the linear carboxylate in the electrolyte is 40%, the weight content of the cyclic carbonate is 10%, the weight content of DFEA is 1%, and the ratio Z of the weight of ethyl 2,2-difluoroacetate to the weight of the linear carboxylate is 0.03.

[0145] The low-temperature capacity retention rate of the lithium-ion battery of Example 7b was measured to be 70.53%.

[0146] Example 7c The method is carried out in accordance with Example 2, except that the weight content of the linear carboxylate in the electrolyte is 40%, the weight content of the cyclic carbonate is 10%, the weight content of DFEA is 20%, and the ratio Z of the weight of ethyl 2,2-difluoroacetate to the weight of the linear carboxylate is 0.5.

[0147] The low-temperature capacity retention rate of the lithium-ion battery of Example 7c was measured to be 75.35%.

[0148] Example 7d The method is carried out in accordance with Example 2, except that the weight content of the linear carboxylate in the electrolyte is 15%, the weight content of the cyclic carbonate is 3.7% (in order to reduce the influence of the change in the weight ratio of the linear carboxylate to the cyclic carbonate on the effect, the weight ratio of the linear carboxylate to the cyclic carbonate can be kept basically unchanged, thereby adjusting the weight content of the cyclic carbonate), the weight content of DFEA is 15%, and the weight ratio Z of ethyl 2,2-difluoroacetate to the weight of the linear carboxylate is 1.

[0149] The low-temperature capacity retention rate of the lithium-ion battery of Example 7d was measured to be 74.33%.

[0150] Example 7e The method is carried out in accordance with Example 2, except that the weight content of the linear carboxylate in the electrolyte is 10%, the weight content of the cyclic carbonate is 2.5% (in order to reduce the influence of the change in the weight ratio of the linear carboxylate to the cyclic carbonate on the effect, the weight ratio of the linear carboxylate to the cyclic carbonate can be kept basically unchanged, thereby adjusting the weight content of the cyclic carbonate), the weight content of DFEA is 20%, and the weight ratio Z of ethyl 2,2-difluoroacetate to the weight of the linear carboxylate is 2.

[0151] The low-temperature capacity retention rate of the lithium-ion battery of Example 7e was measured to be 71.34%.

[0152] Example 7f The method is carried out in accordance with Example 2, except that the weight content of the linear carboxylate in the electrolyte is 25%, the weight content of the cyclic carbonate is 6.2% (in order to reduce the influence of the change in the weight ratio of the linear carboxylate to the cyclic carbonate on the effect, the weight ratio of the linear carboxylate to the cyclic carbonate can be kept substantially unchanged, thereby adjusting the weight content of the cyclic carbonate), the weight content of DFEA is 5%, and the weight ratio Z of ethyl 2,2-difluoroacetate to the weight of the linear carboxylate is 0.2.

[0153] The low-temperature capacity retention rate of the lithium-ion battery of Example 7f was measured to be 76.32%.

[0154] Example 7g The method is carried out with reference to Example 2, except that the weight content of the linear carboxylate in the electrolyte is 10%, the weight content of the cyclic carbonate is 2.5% (in order to reduce the influence of the change in the weight ratio of the linear carboxylate to the cyclic carbonate on the effect, the weight ratio of the linear carboxylate to the cyclic carbonate can be kept basically unchanged, thereby adjusting the weight content of the cyclic carbonate), the weight content of DFEA is 15%, and the weight ratio Z of ethyl 2,2-difluoroacetate to the weight of the linear carboxylate is 1.5.

[0155] The low-temperature capacity retention rate of the lithium-ion battery of Example 7g was measured to be 71.11%.

[0156] Example 7h The method is carried out in accordance with Example 2, except that the weight content of the linear carboxylate in the electrolyte is 10%, the weight content of the cyclic carbonate is 2.5% (in order to reduce the influence of the change in the weight ratio of the linear carboxylate to the cyclic carbonate on the effect, the weight ratio of the linear carboxylate to the cyclic carbonate can be kept substantially unchanged, thereby adjusting the weight content of the cyclic carbonate), the weight content of DFEA is 25%, and the weight ratio Z of ethyl 2,2-difluoroacetate to the weight of the linear carboxylate is 2.5.

[0157] The low temperature capacity retention rate of the lithium ion battery of Example 7h was measured to be 69.87%.

[0158] Example 8 Group This group of embodiments is used to illustrate the impact when D1 / D2 changes, wherein D1 / D2 can be adjusted by changing the diameter of the convex portion, and the proportion of the orthographic projection area of ​​the convex portion on the first surface remains substantially unchanged.

[0159] Example 8a The same process is carried out as in Example 1, except that D1 is 3 mm, D2 is 0.5 mm, and D1 / D2 is 6.

[0160] Example 8b The same process is carried out as in Example 1, except that D1 is 7 mm, D2 is 0.5 mm, and D1 / D2 is 14.

[0161] Example 8c The same process is carried out as in Example 1, except that D1 is 10 mm, D2 is 0.5 mm, and D1 / D2 is 20.

[0162] Example 8d The same process is carried out as in Example 1, except that D1 is 5 mm, D2 is 0.2 mm, and D1 / D2 is 25.

[0163] Example 8e The same process is carried out as in Example 1, except that D1 is 9.7 mm, D2 is 8 mm, and D1 / D2 is 1.21.

[0164] Example 8f The same process is carried out as in Example 1, except that D1 is 9.7 mm, D2 is 0.34 mm, and D1 / D2 is 28.53.

[0165] Example 8g The same process is carried out as in Example 1, except that D1 is 15 mm, D2 is 2.5 mm, and D1 / D2 is 6.

[0166] Example 8h The process is carried out with reference to Example 1, except that D1 is 3 mm, D2 is 0.5 mm, D1 / D2 is 6, and the orthographic projection area of ​​the convex portion on the first surface accounts for 38.7% (in this case, the diameter of the convex portion can be kept basically unchanged).

[0167] Example 9 Group This group of embodiments is used to illustrate the impact produced when the height H of the protrusion changes.

[0168] Example 9a The same process is carried out as in Example 1, except that the height H of the protrusion is 5.8 μm.

[0169] Example 9b The same process is carried out as in Example 1, except that the height H of the protrusion is 18.4 μm.

[0170] Example 9c The same process is carried out as in Example 1, except that the height H of the protrusion is 3.1 μm.

[0171] Example 9d The same process is carried out as in Example 1, except that the height H of the protrusion is 39.5 μm.

[0172] Example 9e The same process is carried out as in Example 1, except that the height H of the protrusion is 43.8 μm.

[0173] Example 9f The same process is carried out as in Example 1, except that the height H of the protrusion is 2.3 μm.

[0174] The expansion rate of the lithium ion battery of Example 9f was measured to be 7.48%.

[0175] Example 10 Group This group of embodiments is used to illustrate the impact produced when the thickness of the first coating layer changes.

[0176] Example 10a The process is carried out in accordance with Example 1, except that the thickness of the first coating layer is 1 μm.

[0177] Example 10b The process is carried out in accordance with Example 1, except that the thickness of the first coating layer is 2.5 μm.

[0178] Example 10c The process is carried out in accordance with Example 1, except that the thickness of the first coating layer is 0.5 μm.

[0179] Example 10d The process is carried out in accordance with Example 1, except that the thickness of the first coating layer is 8 μm.

[0180] Example 10e The process is carried out in accordance with Example 1, except that the thickness of the first coating layer is 0.2 μm.

[0181] Example 10f The process is carried out in accordance with Example 1, except that the thickness of the first coating layer is 8.8 μm.

[0182] Comparative Example 1 The same procedure is carried out as in Example 1, except that there is no convex portion.

[0183] The low-temperature capacity retention rate of the lithium-ion battery of Comparative Example 1 was measured to be 70.42%, and the expansion rate was 8.97%.

[0184] Comparative Example 2 The process is carried out in accordance with Example 1, except that there is no chain carboxylate in the electrolyte.

[0185] The low-temperature capacity retention rate of the lithium-ion battery of Comparative Example 2 was measured to be 68.32%.

[0186] Comparative Example 3 The process is carried out in accordance with Example 1, except that no cyclic carbonate is present in the electrolyte.

[0187] The low-temperature capacity retention rate of the lithium-ion battery of Comparative Example 3 was measured to be 67.34%.

[0188] Comparative Example 4 The same method as in Example 1 is used, except that the weight content of the chain carboxylic acid ester in the electrolyte is 15%, the weight content of the cyclic carbonate is 10%, and the weight content of the chain carboxylic acid ester is adjusted so that the weight ratio of the chain carboxylic acid ester to the cyclic carbonate is 1.5.

[0189] The low-temperature capacity retention rate of the lithium-ion battery of Comparative Example 4 was measured to be 66.62%.

[0190] Comparative Example 5 The same method is carried out in accordance with Example 1, except that the weight content of the chain carboxylic acid ester in the electrolyte is 50%, the weight content of the cyclic carbonate is 5%, and the weight content of the chain carboxylic acid ester is adjusted to a ratio of the weight of the chain carboxylic acid ester to the weight of the cyclic carbonate to be 10.

[0191] The low-temperature capacity retention rate of the lithium-ion battery of Comparative Example 5 was measured to be 67.31%.

[0192] Comparative Example 6 The same procedure is carried out as in Example 1, except that D1 is 8 mm, D2 is 1.9 mm, D1 / D2 is 4.21, and the number of protrusions in an arbitrarily selected area of ​​1 cm×1 cm is 2.

[0193] The low-temperature capacity retention rate of the lithium-ion battery of Comparative Example 6 was measured to be 68.39%.

[0194] Test Case The lithium ion batteries obtained in the embodiment and the comparative example were respectively subjected to the following tests: (1) Cyclic stability test The battery was placed in an ambient temperature of (25±2)℃, charged to 4.45V at a constant current density of 1.5C, and discharged to 3.0V at a constant current density of 0.5C. The discharge capacity was recorded as the initial capacity Q0. One charge and discharge cycle was recorded as 1 cycle. When the cycle reached 500 cycles, the discharge capacity was Q1. The cycle capacity retention rate (%) = (Q1 / Q0) × 100%.

[0195] (2) Low temperature discharge test The battery was placed in an ambient temperature of (25±2)℃, charged to 4.45V at a constant current density of 1.5C, discharged to 3.0V at a constant current density of 0.5C, and the discharge capacity was recorded as the initial capacity Q0. The battery was then charged to 4.45V at a constant current density of 1.5C, and then placed in a 0℃ environment for 30 minutes, and discharged to 3.0V at a constant current density of 0.5C. The discharge capacity was recorded as the low-temperature discharge capacity Q2. The capacity retention rate at low temperature (%) = (Q2 / Q0) × 100%.

[0196] (3) Adhesion test Place the battery in an ambient temperature of (25±2)℃, take out the part where the positive electrode sheet and the separator are bonded to each other in the lithium-ion battery, cut it into 2mm×2mm samples, fold the free end of the sample 180°, and peel off the adhesive surface for about 50mm; fix the two ends of the peeled adhesive surface on both sides of the peel force tester respectively, start the instrument to peel off the free end of the sample, and obtain the adhesive force directly from the test instrument.

[0197] (4) Furnace temperature test The battery is placed in an ambient temperature of (25±2)℃, charged at 0.5C to an upper voltage limit of 4.45V, and a cut-off current of 0.05C. The battery is then placed in a 130℃ / 140℃ thermal shock test chamber, and the temperature is raised to 130℃ and 140℃ at a rate of 5℃ / min±2℃ / min, respectively, and maintained for 60 minutes. When the battery does not smoke, catch fire, or explode, it means it has passed. Test 10 battery samples, and the test results are expressed as "passed test / 10T", for example, "1P / 10T" means that only 1 out of 10 tests passed the test.

[0198] (5) Rate performance test Place the battery at an ambient temperature of (25±2)℃, charge it to 4.45V at a constant current of 1.5C, discharge it to 3.0V at a constant current of 0.5C, record the discharge capacity as the initial capacity Q0, then charge it to 4.45V at a constant current of 1.5C, then discharge it at 2.5C and 5C rates, record the capacities Q4 and Q5, then the capacity retention rate (%) of 2.5C = (Q4 / Q0) × 100%; the capacity retention rate (%) of 5C = (Q5 / Q0) × 100%.

[0199] (6) Expansion rate test Place the battery in an ambient temperature of (25±2)℃, measure the thickness of the battery and record it as L0, charge it to 4.45V at a constant current density of 1.5C, discharge it to 3.0V at a constant current density of 0.5C, and record the discharge capacity as the initial capacity Q0. The above charge and discharge is recorded as one cycle. When the cycle reaches 500 cycles, measure the thickness of the battery at this time and record it as L1. The thickness expansion rate (%) = [(L1-L0) / L0]×100%.

[0200] The obtained results are recorded in Table 1.

[0201] Table 1 As can be seen from Table 1, through the comparative examples and embodiments, it can be seen that the battery of the embodiment has an improved 500-cycle capacity retention rate, the 130°C and 140°C furnace temperature test results are significantly improved, and the 5C rate capacity retention rate is improved, indicating that by providing a convex portion on the positive electrode sheet, the thickness expansion rate is significantly reduced, and at the same time, the density of the convex portions and the relationship between the weight proportions of cyclic carbonate and chain carboxylic acid ester in the electrolyte are controlled, thereby improving the cycle stability, rate performance and safety performance of the battery.

[0202] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is located between the positive electrode sheet and the negative electrode sheet, the separator comprises a carrier layer and a coating layer located on one side or both sides of the carrier layer, the coating layer comprises a first coating layer, the first coating layer is adjacent to the positive electrode sheet, and the first coating layer is distributed on the surface of the carrier layer in a dotted or planar manner; The positive electrode sheet has a first surface and a second surface facing each other in the thickness direction, a plurality of convex portions exist on the first surface of the positive electrode sheet, and concave portions corresponding to the convex portions exist on the second surface, and the ratio of the distance D1 between the centers of adjacent convex portions to the shortest distance D2 between the edges of adjacent convex portions is 1.05-30; The electrolyte includes chain carboxylates and cyclic carbonates, the chain carboxylates include one or more of propyl propionate, propyl acetate, isopropyl acetate, ethyl acetate, ethyl butyrate and methyl propionate, the cyclic carbonate includes propylene carbonate and / or ethylene carbonate, and the weight ratio of the chain carboxylates to the cyclic carbonate is 1.1-10.

2. The battery according to claim 1, wherein The first coating layer comprises one or more of polyethylene oxide, polyethylene wax, polypropylene oxide, polyetherimide, vinylidene fluoride polymer, polyacrylonitrile, acrylate polymer, acrylic polymer and aramid; And / or, the thickness of the first coating layer is 0.5 μm-8 μm; and / or, the ratio of the distance D1 between the centers of adjacent convex portions to the shortest distance D2 between the edges of adjacent convex portions is 1.1-20; And / or, the weight ratio of the linear carboxylic acid ester to the cyclic carbonate ester is 1.5-5.

3. The battery according to claim 1 or 2, wherein: D1 is 2mm-10mm; and / or, D2 is 0.2 mm to 8 mm; And / or, based on the surface area of ​​the carrier layer, the orthographic projection area of ​​the first adhesive layer on the carrier layer accounts for 25%-100%.

4. The battery according to claim 1 or 2, wherein Based on the total weight of the electrolyte, the weight content of the chain carboxylic acid ester is 10%-40%; And / or, based on the total weight of the electrolyte, the weight content of the cyclic carbonate is 5%-35%.

5. The battery according to claim 1 or 2, wherein The electrolyte also includes ethyl 2,2-difluoroacetate, and the weight content of the ethyl 2,2-difluoroacetate is 1%-20% based on the total weight of the electrolyte.

6. The battery according to claim 5, wherein The weight ratio Z of the ethyl 2,2-difluoroacetate to the chain carboxylate is 0.1-2.

7. The battery according to claim 1 or 2, wherein: The height H of the convex portion is 3 μm-40 μm; And / or, the first surface comprises a convex region, and the number of convex portions in an arbitrarily selected area of ​​1 cm×1 cm in the convex region is 2-25; And / or, on the first surface, an area proportion of an orthographic projection of the convex portion on the first surface is 2%-85%.

8. The battery according to claim 1 or 2, wherein: The carrier layer includes a substrate layer and a ceramic layer located on one side or both sides of the substrate layer; the diaphragm satisfies at least one of the following conditions: (1) The substrate layer comprises one or more of polyolefin, polyolefin alcohol, polyamide, polyolefin ester, polydopamine and polyolefin nitrile; (2) The ceramic layer includes inorganic particles, and the inorganic particles include one or more of aluminum oxide, aluminum hydroxide, boehmite, silicon oxide, titanium oxide, barium sulfate, silicon nitride, aluminate, aluminum nitride and zirconium oxide; (3) The thickness of the ceramic layer is 1 μm-8 μm; (4) The thickness of the separator is 2 μm-20 μm.

9. The battery according to claim 1 or 2, wherein the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material layer located on one side or both sides of the negative electrode current collector, wherein the negative electrode active material layer comprises a negative electrode active material, wherein the negative electrode active material comprises one or more of graphite, hard carbon, soft carbon, silicon carbon, silicon oxygen and graphene; and the negative electrode sheet satisfies at least one of the following conditions: (1) The negative electrode active material includes a doping element, and the doping element includes one or more of Fe, Cu, Ca, Ni and Na; (2) The weight ratio of the doping element in the negative electrode active material is 10ppm-80ppm.

10. The battery according to claim 1 or 2, wherein The positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer located on one side or both sides of the positive electrode current collector, wherein the positive electrode active material layer comprises a positive electrode active substance, wherein the positive electrode active substance comprises a lithium cobalt oxide material, and the lithium cobalt oxide material is a doped and / or modified lithium cobalt oxide material; the positive electrode sheet satisfies at least one of the following conditions: (1) The lithium cobalt oxide material includes a chemical formula of LiCo 1-d-e M d N e O2 particles, wherein 0.01≤d≤0.1, 0≤e≤0.05, M includes Mn and / or Al, and N includes one or more of Na, Mg, Zr, Ni, Y, Sr, W, Sc, B, W, Si, Ti, Zr, Sr, Sn, Tb, Nb, Sb, Se, Ce and Te; (2) The median particle size of the lithium cobalt oxide material is 8 μm-25 μm.

Citation Information

Patent Citations

  • Lithium battery

    CN105811010A

  • Pole piece and battery cell

    CN107681116A

  • Battery

    CN114024098A

  • High-voltage lithium cobalt oxide battery and preparation method thereof

    CN116053456A

  • Electrochemical device and electronic device

    CN116802877A

Cited By

  • Battery

    CN121307152A

  • A battery

    CN121307152B